EFFECT OF EXTRACTION ON PHENOILC CONTENT, SILYMARIN AND ANTIRADICAL ACTIVITIES OF ARTICHOKE LEAVES AND ROOTS - Gamil E. Ibrahim; Mohamed A. El-Raey; Omayma A. Eldahshan; Ahmed M. A. Souleman (European Scientific Journal, ESJ, 2013)
Artichoke is a source of biophenols that exhibit lots of pharmacological activities. The aim of the present study is to determine the effect of different extraction methods on the phenolic, and silymarin contents as well as antiradical activities of artichoke leaves and roots. First, the total phenol content was determined by the Folin–Ciocalteu procedure; the gallic acid equivalent values ranged from 16.42-30.28 mg/g. Generally, different leave extracts showed higher contents of phenol than the root extracts. It was found that the methanolic extract of the leaves exhibited the most value of phenolic content (30.28 mg/g) while the root infusion showed the least value (16.42 mg/g). The analysis of silymarin and silybin compounds from each extract was carried out by reversed phase high performance liquid chromatography (RP-HPLC). The infusion extract of leaves showed also the higher content of silymarin than that of root extracts, and the infusion of the leaves exhibited the higher value while the water extract of roots exhibited the least one. Antiradical activities were evaluated using 1, 1-Diphenyl-2-picrylhydrazyl (DPPH0) free radical and β-carotene bleaching methods. Good correlation (R2 =0.9752) was found between phenolic content and antioxidant activity. The minimum EC50 was obtained in the leaves methanol extract that showing value of 16.48 ug/g under the same conditions.According to these results, the use of artichoke extracts is suggested from industrial waste as possible ingredients to functionalize foodstuffs (to decrease lipid peroxidation and to increase health-promoting properties) and as a potential source for pharmacological industries.